The Influence of Motivation, Ability, and Opportunity (MAO) and Strategy on The Use of Auto-Debit in Paying JKN Contributions - Nunki Malahayati; Arif Imam Suroso; Linda Karlina Sari (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: As of August 31, 2025, 32,456,829 Indonesians have registered as PBPU participants, with 47.9% being inactive due to premium payment arrears, totaling IDR 20.1 trillion. The mandatory digitalization (auto-debit) of JKN premium payments for PBPU participants is a management strategy to maintain and increase participant activeness.Purpose: This research aims to analyze the actual behavior and characteristics of PBPU participants that influence their use of digitalization (auto-debit) using the Motivation, Ability, and Opportunity (MAO) theory. It also formulates alternative strategies as recommendations for organizational improvement in refining existing policies.Design/methodology/approach: This research was conducted from January to October 2024 with 300 respondents. The respondents' answers were processed using descriptive analysis, top two boxes and bottom two boxes, crosstabulation, PLS-SEM, and priority/performance matrix.Findings/Results: The results show that the benefits of auto-debit for PBPU participant activeness have the strongest influence on motivation, knowledge about paying mandatory auto-debit premiums has the strongest influence on ability, and knowing information about mandatory auto-debit payments has the strongest influence on opportunity. Meanwhile, the intention to continue using auto-debit has the strongest influence on auto-debit usage.Conclusion: The results indicate that Mandatory auto-debit for JKN premium payments has not been effective in maintaining and increasing PBPU participant activeness. Therefore, management needs to improve educational information provision on auto-debit usage to enhance literacy skills and refine policies that impose sanctions to increase compliance among PBPU participants.Originality/value (State of the art): A systematic, structured, massive, and sustainable JKN campaign program and education effort can be an effective strategy to increase PBPU participants' knowledge and literacy about JKN participation administration, including mandatory auto-debit payments, to enhance participant activeness. Keywords:  PBPU participants, auto-debit, strongest influence, JKN premium, digitalization